Artificial Intelligence In Managing The Electronic Customer Relationship And Enhancing The Level Of Satisfaction With Electronic Services - Mohammad Ali Alqudah; Leyla Muradkhanli (International Journal on Orange Technologies, 2021)
The customer is the backbone of the process of using the applications in the government institution. In a way that ensures the creation of its information about the change of his desires and opinions about the products and applications that are developed by electronic governments, and even his reactions and complaints within a marketing strategy that artificial intelligence sought with its embodied tools for information technology to provide it, and the result was to manage the relationship with the customer using the technological developments that help to do so. Throughout this article, we try to find out the following questions: What The role of artificial intelligence in managing a government institution's customer relationship? For this, we proposed three objectives, how expert systems embody the mechanisms of artificial intelligence within the government institution, while the mechanism of customer relationship management within the government institution is represented, how artificial intelligence has contributed to the success of customer relationship management to the e-government